Fulfilling modern astrophysical observations and lattice QCD constraints based on a nonlocal NJL model with 3D form factor - Contrera, Gustavo Aníbal Gabriel (2023)
In the present work, we employ a nonlocal Nambu?Jona?Lasinio (NJL) model with a Gaussian form factor that is dependent on the spatial components of the momentum (3D-FF). Focusing on the temperature-baryon chemical potential plane, we investigate some aspects of the phase diagram. Initially, we propose an assumption that the range of interactions in momentum space may be modified by temperature, allowing us to obtain the critical temperature values based on lattice QCD (LQCD) predictions. Subsequently, we consider this model within a hybrid framework to examine the effects of temperature, together with neutrino trapping, in compact object configurations.